Identifikasi Tingkat Berpikir Geometri Siswa Berdasarkan Teori Van Hiele - Azwar Anwar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to describe and identify students' level of thinking in doing questions based on Van Hiele's theory and to give an idea to teachers to be able to use learning methods in accordance with Van Hiele's level of thinking at IBNU Abbas Tarakan IT Junior High School. The method used in this research is a combination method (qualitative & qualitative) with sequential model. The research instruments used were tests on Van Hiele's geometry levels, and interview guidelines. Based on the results of the study obtained 3 students were in pre visualization or have not reached Van Hiele's thinking level, 6 students are at level 1 (visualization), 9 students are at level 2 (analysis), and 3 students are at level 3 (informal deduction). Based on interviews students still have difficulty in understanding the relationship between wakes as well as elements in geometry such as theorem, axiom, and definition. In conclusion, Van Hiele's geometry thinking level at Ibnu Abbas IT Junior High School is generally at level 2, namely the analysis stage and has not reached level 4 (informal deduction). Keywords: Geometry, Level of thinking, Van Hiele Theory